(untitled) (Revista Brasileira Multidisciplinar, 2025)
Abstract: The average food waste in households is approximately 41.6 kg per person per year. This waste mainly occurs due to inadequate management throughout the entire production and consumption chain. Among the improperly discarded materials are fruit and vegetable peels, which have great potential for reuse. These types of waste are rich in bioactive compounds, such as carotenoids, which possess antioxidant activities and provitamin A properties. Aiming at the reuse of this waste, the present study extracted β-carotene, a compound from the carotenoid group, from carrot peels and incorporated it into oil-in-water emulsions. The produced emulsion underwent physical-chemical stability tests, such as centrifugation, preliminary stability, organoleptic characteristics, pH, and density, as well as microbiological evaluation. The results showed that the emulsion is stable, with no evidence of degradation-related alterations, and its microbiological load is within the limits established by current legislation. Therefore, the use of β-carotene extracted from discarded carrots in emulsions proved to be promising in terms of both physical-chemical and microbiological stability. Keywords: Carrot waste; Carotenoids; Emulsion systems; Stability.